β(2)-Adrenoceptor agonists alleviate neuropathic allodynia in mice after chronic treatment - Choucair-Jaafar, Nada (Blackwell Publishing Ltd, 2009)
BACKGROUND AND PURPOSE: Antidepressants are a first-line treatment against neuropathic pain. We previously demonstrated that β(2)-adrenoceptors are necessary for antidepressants to exert their anti-allodynic action. The aim of the present study was to assess whether β(2)-adrenoceptor agonists could be sufficient to alleviate neuropathic allodynia. EXPERIMENTAL APPROACH: We used a murine model of neuropathy induced by unilateral sciatic nerve cuffing in C57BL/6J mice. We previously demonstrated that this animal model is sensitive to chronic, but not to acute, treatment with antidepressant drugs, which is clinically relevant. The mechanical allodynia was evaluated using the von Frey filaments. KEY RESULTS: We showed that chronic but not acute treatment with the β-adrenoceptor agonists, bambuterol, isoprenaline, fenoterol, salbutamol, salmeterol, terbutaline or ritodrine suppressed mechanical allodynia. We confirmed that the action of these β-adrenoceptor agonists was mediated through β(2)-adrenoceptors by blocking it with intraperitoneal or intrathecal, but not intracerebroventricular or intraplantar, injections of the antagonist ICI118551. We also showed that chronic treatments with the β-adrenoceptor antagonists, propranolol or ICI118551 did not suppress the allodynia. CONCLUSIONS AND IMPLICATIONS: Our data show that chronic treatment with β-adrenoceptor agonists has the same antiallodynic properties as treatments with antidepressant drugs. This study was, however, conducted in an animal model, and a clinical validation will be required to confirm the value of the present findings in patients.